Are Retirees More Satisfied? Anticipation and Adaptation Effects of Retirement on Subjective Well-Being: A Panel Analysis for Germany - Joachim Merz (Institute of Labor Economics (IZA), 2018)
Quality of life and satisfaction with life are of particular importance for individuals as well as for society concerning the "demographic change" with now longer retirement periods. This study will contribute to the life satisfaction discussion and quantifies life satisfaction and pattern of explanation before and after such a prominent life cycle event, the entrance into retirement. In particular, with the individual longitudinal data and 33 waves of the Socio-Economic Panel (SOEP) and the appropriate microeconometric causal fixed effects robust panel methods we ask and quantify if actual life satisfaction indeed is decreasing before retirement, is increasing at the entrance into retirement, and is decreasing then after certain periods back to a foregoing level. Thus, we ask if such an anticipation and adaptation pattern – as known from other prominent events – is also to discover for life satisfaction before and after retirement in Germany.
Keywords: I31; J26; J14; J17; A13; C23; 330; retirement; life-satisfaction; happiness; retirement; anticipation and adaptation effects; fixed-effect regression; Socio-Economic Panel (SOEP); Germany